( | 2 | x | − | 1 | ) | ÷ | 3 | − | ( | 4 | x | + | 2 | ) | ÷ | 5 | = | - | 1 |
Left side of the equation = | 2 | x | × | 1 3 | − | 1 | × | 1 3 | − | ( | 4 | x | + | 2 | ) | × | 1 5 |
= | 2 3 | x | − | 1 3 | − | ( | 4 | x | + | 2 | ) | × | 1 5 |
= | 2 3 | x | − | 1 3 | − | 4 | x | × | 1 5 | − | 2 | × | 1 5 |
= | 2 3 | x | − | 1 3 | − | 4 5 | x | − | 2 5 |
= | - | 2 15 | x | − | 11 15 |
- | 2 15 | x | − | 11 15 | = | - | 1 |
- | 2 15 | x | = | - | 1 | + | 11 15 |
- | 2 15 | x | = | - | 4 15 |
4 15 | = | 2 15 | x |
2 15 | x | = | 4 15 |
x | = | 4 15 | ÷ | 2 15 |
= | 4 15 | × | 15 2 |
= | 2 | × | 1 |
x | = | 2 |